Health economic evaluation of Human Papillomavirus vaccines in women from Venezuela by a lifetime Markov cohort model. (December 2017) - Bardach, Ariel; Garay, Osvaldo; Calderón, María; Pichón-Riviére, Andrés; Augustovski, Federico; Martí, Sebastián; Cortiñas, Paula; Gonzalez, Marino; Naranjo, Laura; Gomez, Jorge; Caporale, Joaquín
Abstract Background Cervical cancer (CC) and genital warts (GW) are a significant public health issue in Venezuela. Our objective was to assess the cost-effectiveness of the two available vaccines, bivalent and quadrivalent, against Human Papillomavirus (HPV) in Venezuelan girls in order to inform decision-makers. Methods A previously published Markov cohort model, informed by the best available evidence, was adapted to the Venezuelan context to evaluate the effects of vaccination on health and healthcare costs from the perspective of the healthcare payer in an 11-year-old girls cohort of 264, 489. Costs and quality-adjusted life years (QALYs) were discounted at 5%. Eight scenarios were analyzed to depict the cost-effectiveness under alternative vaccine prices, exchange rates and dosing schemes. Deterministic and probabilistic sensitivity analyses were performed. Results Compared to screening only, the bivalent and quadrivalent vaccines were cost-saving in all scenarios, avoiding 2, 310 and 2, 143 deaths, 4, 781 and 4, 431 CCs up to 18, 459 GW for the quadrivalent vaccine and gaining 4, 486 and 4, 395 discounted QALYs respectively. For both vaccines, the main determinants of variations in the incremental costs-effectiveness ratio after running deterministic and probabilistic sensitivity analyses were transition probabilities, vaccine and cancer-treatment costs and HPV 16 and 18 distribution in CC cases. When comparing vaccines, none of them was consistently more cost-effective than the other. In sensitivity analyses, for these comparisons, the main determinants were GW incidence, the level of cross-protection and, for some scenarios, vaccines costs. Conclusions Immunization with the bivalent or quadrivalent HPV vaccines showed to be cost-saving or cost-effective in Venezuela, falling below the threshold of one Gross Domestic Product (GDP) per capita (104, 404 VEF) per QALY gained. Deterministic and probabilistic sensitivity analyses confirmed the robustness of these results.